Desain Perancangan kwh meter Digital Berbasis Sistem SCADA pada Pelanggan Tegangan Menengah 20 KV di PT PLN (Persero) APJ Jember - H.R.B. Moch. Gozali (Universitas Syiah Kuala, 2011)
SCADA is a very powerful new technology to be applied as a tele-metering. Planning of Digital KWH Meter based on SCADA at 20 kV medium voltage customer isselected in the PLN APJ Jember, where KWH Meters arewidely used today is the Landis Gyr ZMC405C type. But it is less reliable devices along with the development of technology today. KWH Meter ZMD405CT offers more features for modern, effective and efficient to be used by PLN in the future. Design of SCADA in ZMD405CT not use a lot of cable, so they are efficient in terms of cost. Meanwhile, software for data acquisition must be balanced with the KWH meter to be used, for electrical energy measurement accuracy on the customer side can be assured.